The comparison study of PD measurement with conventional method and unconventional method - Petchphung, Prawit; Leelajindakrairerk, Monthon; Pattanadech, Norasage; Yutthagowith, Pearawut; Aunchaleevarapan, Kraision (My University, 2008)
This paper represents the VHF/UHFpartial discharge measurement technique compared with conventional partial discharge measurement method, IEC 60270. The artificial partial discharge objects which represent corona discharge, internal discharge, and surface discharge, were set up and tested with the mention techniques. The test results show that three kinds of partial discharge give obviously different frequency signal obtained from vertical and horizontal VHF/UHF antenna. Its amplitude also depends on electric field stress of the test objects. Moreover the partial discharge activities of all kinds of test object obtained from conventional method are different. From the test results, it was found that unconventional partial discharge measurement technique, VHF/UHF method, can be an effective choice for partial discharge measurement. It also can be improved for online monitoring of insulation system in the future.Keywords:Partial discharge,Antenna, UHF,Coupling device. ©2007 IEEE.
Keywords: Current transformers; Frequency response; Partial discharges